Extended stability study of an extemporaneously analgesic solution of clonidine, ropivacaine and fentanyl - Alessandra Moreira de Oliveira; Jose Carlos Saraiva Gonçalves; Rita de Cássia Elias Estrela (Brazilian Journal of Pharmaceutical Sciences, 2023)
Abstract The aim of this work was to perform an extended stability study for the analgesic containing fentanyl, clonidine and ropivacaine in physiological saline solution 0.9% at different infusion sites, such as infusion bags, epidural infusion sets and syringes. The extended stability was assessed by an HPLC system equipped with a photodiode array detector set at 210 nm. The separation was conducted on a C18 column maintained at 40˚C and using an isocratic mobile phase consisted of buffer solution-methanol-acetonitrile (45:45:10, v/v/v). The presence of particulate matter and the pH of each solution were also investigated. Twenty-four hours after the preparation, the formation of one suspected product was observed and for all drugs, in 24 hours it was observed the concentration decrease in different sets (PVC infusion bags, syringes and epidural infusion administration sets). The pH values of each solution varied no more than 5% during the study and no particle was observed. Conclusion: The extended stability study was applied to the analgesic solution and promoted the detection of an unexpected peak in 24 hours. Based on it, further stability studies are necessary to determine the extended stability data.